A cross-river tunnel excavation considering the water pressure effect based on DEM. Issue 11 (29th September 2021) - Zhang, Zhihua; Zhang, Xiedong; Sun, Shi; Liang, Zhishui
Abstract: A heavy rainy season can result in many disasters, such as a dam collapsing and the water level of a river rising. A cross-river tunnel, as an underground structure, will also be affected by the heavy rain. The discrete element method (DEM), as a main mechanical approach, has unique advantages that allow it to determine the large deformation and stress distribution of discrete particles. Referring to many studies, most of which use the finite element method, a cross-river tunnel model is proposed based on DEM in this article. Different in situ strata and high water pressures due to normal and flood water levels are considered to analyse the characteristics of a high-stress tunnel under deformation and stress conditions. The excavation disturbance zone (EDZ), radial and hoop stresses, radial displacement, porosity of the surroundings and bending moment of concrete lining are considered. The results show that the main deformation of surrounding strata is focused on the vault of the tunnel, stress release occurs at the vault, and porosity and radial displacement increase as the consolidation time increases; more cracks form at the outer edge of the lining under FWP, which will exacerbate the lining deterioration and may lead to disasters.